Impact of pulsatile flow on vital organ recovery during cardiopulmonary bypass in neonates and infants - Ündar, Akif; Wang, Shigang; Palanzo, David; Wise, Robert; Woitas, Karl; Baer, Larry; Kunselman, Allen; Song, Jianxun; Alkan Bozkaya, Tijen; Akçevin, Atıf; Spencer, Shannon; Ağırbaşlı, Mehmet Ali; et al. (Wiley-Blackwell, 2016)
Despite advances in surgical techniques and medical management, congenital heart defects still have a significant impact on morbidity, mortality, and healthcare costs. Based on the Society of Thoracic Surgeon’s Fall 2014 database, neonates (0–30 days) have the highest congenital heart surgery mortality rate of 9.6% (9.1–10.1%), while infants (31 days to 1 year) 3.0% (2.8–3.2%) and children (>1 year–18 years) 1.1% (1.0–1.2%) follow over the last 4 years (1). Vital organ injury during and after neonatal and infant cardiopulmonary bypass (CPB) procedures is considered to be a main cause (2–5). The reasons for this are multifactorial. Hundreds of articles have already been published on the major causes including systemic inflammatory response syndrome, deep hypothermic circulatory arrest, ischemia/reperfusion injury, hematocrit levels, degree of hypothermia, pH versus alpha stat strategies, and nonpulsatile versus pulsatile perfusion (6–8). Among them, perfusion mode is still a matter of controversy.
Keywords: Impact of Pulsatile; Flow on Vital Organ; Recovery During; Cardiopulmonary Bypass; Neonates and Infants